2008
DOI: 10.1149/1.2823262
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Gallium Electrode Confined in Porous Carbon Matrix as Anode for Lithium Secondary Batteries

Abstract: A liquid gallium electrode confined in a porous carbon matrix was prepared by vaporization and pyrolysis of Ga͑III͒-phthalocyanine chloride on a nanosized Ga 2 O 3 powder surface, which was followed by carbothermal reduction of Ga 2 O 3 by a carbon matrix. When the electrode was charge/discharge cycled, the liquid Ga component was restored to its original liquid state at the final stage of delithiation, such that any electrode failure modes, for instance, crack formation and electric disconnection that are cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…1. With respect to reaction (2), the electrochemical characteristics below 1.0 V observed in the present study are similar to those for a Li-Ga system reported previously [23,24]. These findings support the notion that reactions (1) and (2) occur at the higher and lower potentials, respectively, during lithiation and delithiation.…”
Section: Discussionsupporting
confidence: 91%
“…1. With respect to reaction (2), the electrochemical characteristics below 1.0 V observed in the present study are similar to those for a Li-Ga system reported previously [23,24]. These findings support the notion that reactions (1) and (2) occur at the higher and lower potentials, respectively, during lithiation and delithiation.…”
Section: Discussionsupporting
confidence: 91%
“…In some early explorations, the electrode property of the Ga metal was studied as a Li-ion anode, but due to the slightly higher than room temperature melting point of Ga metal (29.8 °C), the extra energy input was still necessary. 60 , 61 Besides, since the transport and reaction kinetics of the solidified electrode is more sluggish than in the liquid phase, the bulk Ga electrode shows relatively low cyclability. 62 …”
Section: Room-temperature Liquid Metal Batteriesmentioning
confidence: 99%
“…The hybridization between active materials and carbon matrix, particularly porous carbon, is also proved potent to alleviate the volume changes, provide efficient ion diffusion in its porous channels and strengthen the electrical contact between active materials and current collector. Lee et al reported a carbothermal reduction of Ga 2 O 3 nanoparticles to prepare nano Ga confined in porous carbon (Ga-C) [103]. Voltage profiles recorded at 55°C for pure Ga and Ga-C electrodes revealed that Ga-C anode held a lower lithiation voltage, indicating the larger lithiation overpotential being involved.…”
Section: Gallium Metal Anodesmentioning
confidence: 99%